2011
DOI: 10.1176/appi.neuropsych.23.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia in Psychotic Patients: Clinical Features and Treatment Response

Abstract: We report clinical features and treatment response in 25 patients with catatonia admitted to an inpatient psychiatric unit specializing in psychotic disorders. ECT, benzodiazepines, and clozapine had beneficial effects on catatonic features, while typical antipsychotics resulted in clinical worsening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…Benzodiazepines, and especially lorazepam, are the drugs of choice for the acute management of catatonia, and they are widely used for this purpose17 given their mechanism of action through the GABA-A receptor. There is plenty of literature on the effectiveness of lorazepam in catatonia of various aetiologies, mainly case reports, series and open label studies,27 36 37 but to date there is no evidence from randomised controlled trials of its use in catatonia secondary to schizophrenia 38. In this illness, there is controversy on the role of antipsychotic drugs in the management of catatonia, with some authors suggesting that they worsen the latter (except for clozapine)37 while others reporting that they can be beneficial 27 39.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzodiazepines, and especially lorazepam, are the drugs of choice for the acute management of catatonia, and they are widely used for this purpose17 given their mechanism of action through the GABA-A receptor. There is plenty of literature on the effectiveness of lorazepam in catatonia of various aetiologies, mainly case reports, series and open label studies,27 36 37 but to date there is no evidence from randomised controlled trials of its use in catatonia secondary to schizophrenia 38. In this illness, there is controversy on the role of antipsychotic drugs in the management of catatonia, with some authors suggesting that they worsen the latter (except for clozapine)37 while others reporting that they can be beneficial 27 39.…”
Section: Managementmentioning
confidence: 99%
“…There is plenty of literature on the effectiveness of lorazepam in catatonia of various aetiologies, mainly case reports, series and open label studies,27 36 37 but to date there is no evidence from randomised controlled trials of its use in catatonia secondary to schizophrenia 38. In this illness, there is controversy on the role of antipsychotic drugs in the management of catatonia, with some authors suggesting that they worsen the latter (except for clozapine)37 while others reporting that they can be beneficial 27 39. It would appear that antipsychotics with strong D2 receptor antagonism should be avoided in patients with psychosis and catatonia 37.…”
Section: Managementmentioning
confidence: 99%
“…9,10 Significant dopamine blockade can also cause catatonia. England et al 11 reported that first-generation antipsychotic medications caused worsening catatonia symptoms. However, second-generation antipsychotic medication on several occasions did treat the symptoms of catatonia.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Even though NMS was described in some catatonic patients treated with clozapine, 8 this medication has been shown to be more efficient than other APs for the treatment of chronic catatonia with schizophrenia, although most of the studies reported on a small number of cases. [10][11][12] In line with the usual recommendation for clozapine initiation, the treatment requires a baseline evaluation, slow titration and close monitoring.10 A daily dose between 300 and 750 mg may be required to achieve efficacy, 10,11 and relief from catatonic symptoms is observed within 2-7 weeks of treatment. …”
mentioning
confidence: 99%
“…10 A daily dose between 300 and 750 mg may be required to achieve efficacy, 10,11 and relief from catatonic symptoms is observed within 2-7 weeks of treatment. [10][11][12] The neurobiology of catatonia is complex, [13][14][15] and clozapine may be effective through its actions at various biological junctures of this neurobiology. 10,16 It is possible that the net effect of clozapine on dopamine neurotransmission (low D2 receptor occupancy coupled with increased dopamine release in the striatum via the stimulation of 5-HT 1A receptors) contributes to the anticatatonic effects of clozapine.…”
mentioning
confidence: 99%